Why the Increase in the Retirement Age Will Lead to More Inequality and Poverty? An Ignored Fairness Problem - Stauvermann, Peter J.; Kumar, Ronald R.; Patel, Arvind (Panoeconomicus, 2023)
In this study, we show with the help of a simple model that an increase of the retirement age has a negative impact on the distribution of pension benefits in the Bismarckian as well in the Beveridgean pension system. In both systems, the distribution of pension benefits will change in favour of high-income earners. Additionally, we show that the increasing gap in the life expectancies of low and high-income earners will increase inequality. Both results are a consequence of the positive relationship between the socio-economic status and life expectancy of a person. These important insights are often ignored by the promoters of pension reforms. JEL: H55, D31.